Chants in EFL Vocabulary Instruction with Young Learners: Potential, Composition and Application - Cindy Cedeño; Luis Santos (Journal of English Language Teaching and Linguistics, 2021)
Songs and chants in EFL education are both artistic and pedagogical acts belonging to the same family of musical expressions, whose practical use in the classroom is not unfamiliar among teachers. Nevertheless, little effort has been made to distinguish between each other. In this sense, the popularity of songs in the context of EFL/ESL education is well-manifested in research, especially in the context of young learners’ teaching, yet little has been said regarding chants on formal studies. The nature of chants entails a less complex musical composition, which lends itself to favoring language development both receptively and productively. While both singing and chanting as pedagogical resources are found positive in learning a new language in aspects such as phonological awareness, pronunciation, word retrieval, and other linguistic functions; it seems that chanting works exceptionally well for stimulating young learners’ vocabulary retention, which is a capacity associated with long-term memory. The ease and novelty of conveying language in an unconventional fashion allowed by chanting, afford for simplified and fun repetitions and production of the target language, which may represent the virtues responsible for its positive impact on the young learners’ vocabulary learning. Practical recommendations for composing chants and guiding teaching activities based on them are explained.